Exercise training improves activity in adolescents with congenital heart disease. Issue 15 (7th June 2013) - Morrison, M L; Sands, A J; McCusker, C G; McKeown, P P; McMahon, M; Gordon, J; Grant, B; Craig, B G; Casey, F A
Abstract : Objectives: To ascertain if motivational techniques and a structured exercise programme can increase activity in adolescents afflicted with congenital heart disease (CHD). Design: Prospective randomised controlled trial. Setting: One hundred and forty-three patients aged 12–20 years attending the tertiary centre for paediatric cardiology in Northern Ireland. Main outcome measures: Increase in exercise capacity as assessed by duration of exercise stress test, and number of minutes spent in moderate to vigorous physical activity (MVPA) per day. Results: Eighty-six patients were men (60%), mean age was 15.60±2.27 years. Seventy-three percent were considered to have major CHD. Seventy-two participants were randomised to the intervention group. Following intervention, duration of exercise test increased by 1 min 5 s for the intervention group (p value 0.02) along with increase in predicted VO2Max (p value 0.02). There was a significant increase in minutes of MVPA per day for the intervention group from baseline to reassessment (p value <0.001) while MVPA remained much the same for the control group. Fourteen patients met the current recommendation for more than 60 min MVPA per day at baseline. This doubled to 29 participants at reassessment. There were no adverse effects or mortalities reported. Conclusions: Exercise training is safe, feasible and beneficial in adolescents with CHD. Psychological techniques can be employed to maximise the impact of interventions. Trial Registration Number: ISRCTN27986270.